CONTEMPORARY ASPECTS REGARDING THE ETIOLOGY OF GINGIVAL RECESSIONS. A REVIEW. - Ioannis Kanarakis; Darius Sandu; Sorina Mihaela Solomon; Liliana Pasarin; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Ioana-Andreea Sioustis; Diana-Cristala Kapp; Ionut Luchian (Romanian Society of Oral Rehabilitation, 2021)
Gingival recession is one of the most frequent undesirable conditions of the periodontal tissues, affecting a significant number of adult individuals worldwide. Gingival recessions can be the result of many etiological factors and occur, due to different factors acting simultaneously. Plaque-induced recession, can be recovered by surgical root coverage procedures, if it does not advance to the interdental papillae, while the periodontitis-related recession is harder to be restored. The most common traumatic etiologic factor, and one of the most common etiologic factors in general, is brushing-induced trauma. Another factor that can, in specific occasions, lead to gingival recession, is occlusal trauma. In general, abnormal occlusion is not a causative factor for recession. The reason is that there is no scientific evidence proving this relationship and that, after surgical treatment of the recession without fixing the pathological occlusion, there is no recurrence. Orthodontic patients have increased probability to form gingival recessions and, hence, orthodontic therapy is a major predisposing factor, especially at the area of mandibular incisors. Furthermore, prosthetic treatment is an iatrogenic predisposing factor of gingival recessions, due to trauma, either during impression taking, or during abutment preparation. Yet, there are some cases of gingival recessions that are not caused by the etiologic factors described above and, therefore, they are considered recessions of unknown etiology. These lesions are manifested as bright red inflammation of the tissue, surrounding the clinically visible roots. Gingival recessions are difficult to treat especially whenever the etiology is not clear. For a favorable prognosis is essential to identify specifically the etiological factors and correct them prior the surgical treatment.